Burnout syndrome among hotel employees: The case of the city of Konya - Adnan Celik; Cagri Sacli (Economic and Environmental Studies (E&ES), 2013)
The aim of this study is to find out the level of burnout of employees who work at the 4- and 5-star hotels in Konya (Turkey), and whether hotel employees' mean scores' of burnout sub dimensions vary according to their demographic characteristics. For this aim, a survey that consists of Maslach Burnout Inventory and personal information form is applied in 8 hotel enterprises. Data that are obtained from surveys are analyzed by using statistical software (SPSS 16.0). During the analyses, reliability analysis, independent sample t- tests and one- way ANOVA tests are performed. The findings of the study indicated that hotel employees' level of emotional exhaustion is medium, level of depersonalization is low, and, level of personal accomplishment is high.
Keywords: 330; burnout syndrome; hotel employees; Konya; Turkey